VD_FINDINFO HC / 2023 / 251 vom 27. April 2023 - VD Tribunal cantonal (2023)
PROTECTION DE L'UNION CONJUGALE, GARDE ALTERNÉE, OBLIGATION D'ENTRETIEN, DÉBUT | 176 al. 1 ch. 1 CC, 176 al. 1 ch. 2 CC, 285 CC